Costs or Benefits? Competing Frames and Public Support for Multilateral Peace Operations - Andrew Lugg; Jared Oestman (International Studies Perspectives, 2026)
Abstract Public discourse about international cooperation contains conflicting messages about the desirability of acting through international organizations such as the United Nations (UN). Yet we lack a clear understanding of how individuals evaluate competing frames about the benefits and costs of cooperation. To address this, we field a preregistered survey experiment on public opinion in the United States (US) toward UN peacekeeping, which is one of the UN’s most consequential and contested activities. Respondents receive two competing frames: one emphasizing the benefits of a peacekeeping operation, which vary by who stands to benefit, and another emphasizing the sovereignty costs or opportunity costs of the operation to the US. We find that baseline support for peacekeeping is high when the operation is defined as successful, but that the sovereignty and opportunity cost frames diminish support. Moreover, additional benefit frames, such as those emphasizing benefits to the US, do not increase support above the baseline. We also find that sequencing matters: respondents who encounter a cost frame first have lower support than those who encounter a benefit frame first. Our results contribute to research on the politicization of multilateral cooperation, suggesting that cost-based frames pose a challenge for proponents of multilateral cooperation.